Financial Analysis of Catching Mini Purse Seine Business in Rembang Regency, Central Java - Prawoto, Adi Guno (Journal of Fisheries Resources Utilization Management and Technology, 2023)
Rembang Regency is an area located in the north of Central Java Province which has high fisheries and marine potential. This research was conducted from March 23, 2021 to April 4, 2021 in Rembang Regency, which is located in Karanganyar Village, Pandangan Village, and Bajingmeduro Village. This research method used a descriptive method that is a case study, and the sampling method used the snowball sampling method with 90 respondents with each of Pandangan Village as many as 30 people, Karanganyar Village 40 people, and Bajingmeduro Village as many as 20 people. Capture fisheries mini purse seine in Rembang Regency. The analytical method used in this study is the method of analyzing financial aspects and business feasibility, namely NPV, IRR, B/C ratio and Payback Period (PP). The fishing fleet used is a ship with a size of < 30 GT. The results of the sequential analysis are as follows, the average capital (Pandangan Village, Karanganyar Village, and Bajingmeduro Village) is Rp. 923,333,333; Rp. 946,500,000; and Rp. 1.009.000.000. Total cost (Pandangan Village, Karanganyar Village, and Bajingmeduro Village) is Rp. 1,114,569,119; Rp. 1,146,474,329; and Rp. 1,170,682,052. The average income (Pandangan Village, Karanganyar Village, and Bajingmeduro Village) is Rp. 1,673,529,133; Rp. 1,496,301,750; and Rp. 1,555,515,100. The average profit (Pandangan Village, Karanganyar Village, and Bajingmeduro Village) is Rp. 558,960,014; Rp. 349,827,421; and Rp. 384,833,048. The NPV (Pandangan Village, Karanganyar Village, and Bajingmeduro Village) is Rp. 891,239,529; Rp. 808.052501; and Rp. 802,480,579. IRR (Pandangan Village, Karanganyar Village, and Bajingmeduro Village) of 29%; 29%; and 28%. B/C ratio (Pandangan Village, Karanganyar Village, and Bajingmeduro Village) of 1.59; 1,2; and 1.34. and PP (Pandangan Village, Karanganyar Village, and Bajingmeduro Village) of 4 years 2 months 19 days; 3 years 6 months 18 days; and PP 4 years 5 months 26 days. Capture fisheries mini purse seine in Rembang Regency (Pandangan Village, Karanganyar Village, and Bajingmeduro Village) it is feasible to continue.